Reduksi dosis radiasi pemeriksaan femur dengan bioplastik timbal: pendekatan citra dan anatomi - Alvin Fachrully Septiano; Oktarina Damayanti (JURNAL TERAS KESEHATAN, 2025)
X-ray radiation plays a vital role in medical diagnostics but carries potential risks for both patients and healthcare workers. This study evaluates the effectiveness of cassava starch–based bioplastic combined with lead acetate as an absorber of radiation dose during femur radiographic examinations. The tests were performed using Anteroposterior (AP) and Lateral projections with both portrait and diagonal detector positions. Image processing applied the Gaussian High Pass Filter (GHPF) method at cut-off frequencies of 5, 10, and 15 Hz. Image quality was analyzed through Contrast to Noise Ratio (CNR) and Peak Signal to Noise Ratio (PSNR). Results showed that the use of bioplastic slightly decreased CNR and PSNR values compared to examinations without bioplastic; however, the quality remained within acceptable diagnostic standards. For example, in AP diagonal projection at 5 Hz, CNR reached 22.86 (with bioplastic) versus 21.95 (without), while PSNR values were 11.1 and 11.6, respectively. Increased Mean Square Error (MSE) values confirmed radiation attenuation, supporting effective shielding. Optimal image quality occurred at 5–10 Hz cut-offs, while 15 Hz produced misleading impressions of osteoporosis. Overall, lead-based bioplastic effectively reduces radiation dose while preserving diagnostic value, offering a safer and eco-friendly alternative in radiographic imaging.